Glucose Restriction Inhibits Skeletal Myoblast Differentiation by Activating SIRT1 through AMPK-Mediated Regulation of Nampt - Fulco, Marcella (2008)
It is intuitive to speculate that nutrient availability may influence differentiation of mammalian cells. Nonetheless, a comprehensive complement of the molecular determinants involved in this process has not been elucidated yet. Here, we have investigated how nutrients (glucose) affect skeletal myogenesis. Glucose restriction (GR) impaired differentiation of skeletal myoblasts and was associated with activation of the AMP-activated protein kinase (AMPK). Activated AMPK was required to promote GR-induced transcription of the NAD(+) biosynthetic enzyme Nampt. Indeed, GR augmented the Nampt activity, which consequently modified the intracellular [NAD(+)]/[NADH] ratio and nicotinamide levels, and mediated inhibition of skeletal myogenesis. Skeletal myoblasts derived from SIRT1(+/−) heterozygous mice were resistant to the effects of either GR or AMPK activation. These experiments reveal that AMPK, Nampt, and SIRT1 are the molecular components of a functional signaling pathway that allows skeletal muscle cells to sense and react to nutrient availability.